Development of the active ingredient composition of hand antiseptics in Germany from 2004 to 2022 with special consideration of ethanol as active agent - Grashoff, Philine; Mutters, Nico Tom; Kramer, Axel; Ilschner, Carola; Rausch, Marvin; Gebel, Jürgen (GMS Hygiene and Infection Control)
Aim: The number of active agents used in hand antiseptics (HA) in Germany was analyzed using the disinfectant lists of the Association for Applied Hygiene (VAH) for the years 2004, 2012 and 2022 to evaluate the development regarding the use of unnecessary or critical active agents in alcohol-based hand rubs (ABHR). Results: While 20 different active agents were used in the HAs (97 listed HAs) in 2004, only 14 were used in 2012 (201 listed HAs) and 15 in 2022 (332 listed HAs). Benzoic acid, clorocesol, chlorophene, octenidine dihydrochloride, peracetic acid, polihexanide and triclosan are no longer used as additives to ABHR. At the same time, the number of active ingredients per product fell. In the period from 2002 to 2022, there was an increase in ABHR, so that in 2022, only four HAs did not contain alcohol: three were based on PVP iodine and one was based on quaternary ammonium compounds. While 2-propanol still dominated as the first-named active ingredient in 2004 and 2022, in 2022 mainly ABHR with ethanol as the first-named active ingredient were certified. The percentage share of ethanol in ABHR, measured against all VAH-listed HA and as the main active ingredient, increased by 43.4% between 2004 and 2022. At the same time, there has been a 33.2% decrease in ABHR of 2-propanol as active ingredient. Discussion: There are probably two reasons for the decrease in the total number of active ingredients used. The addition of antiseptic agents to ABHR does not increase their residual effectiveness. In addition, the antimicrobial antiseptics added to ABHR are less well tolerated than alcohols. Consequently, for ethical reasons it makes sense not to add these antimicrobials to the formulas. The increase of ethanol-based hand rubs (EBHR) suggests that these are preferred by users. One explanation may be that, unlike ethanol, 1-propanol can have an irritating effect on both healthy and atopic skin. Conclusion: Ethanol must be retained as an active ingredient for ABHR for the following reasons: ethanol is the only active ingredient that can be used for HA with comprehensive efficacy against non-enveloped viruses; both propanols are less physiological for the human organism than ethanol; ethanol is better tolerated by the skin than 1-propanol; and an adverse effect on the skin microbiome has been ruled out for ethanol. This must be considered when discussing the possible biocide classification of ethanol as CMR, especially because such a classification has absolutely no scientific basis.